2023
DOI: 10.1002/leap.1562
|View full text |Cite
|
Sign up to set email alerts
|

Is ORCID your ID? A case study at the Faculty of Arts and Humanities of the University of Porto

Abstract: Author disambiguation has been a key component of scientific communication since the mid‐19th century, and now more than ever. This paper discusses the use of ORCID as a digital identity platform in Social Sciences and Humanities, by analysing the adoption of ORCID in the Faculty of Arts and Humanities of the University of Porto using a manual‐qualitative method. The results show a discrepancy between the use of ORCID as an ID and as an author record. Even though 90.4% of the sample studied had an ORCID iD, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…In Portugal, the Faculty of Arts and Humanities at the University of Porto showed a high ORCID adoption rate (90.4%), but the records were often incomplete, impacting the disambiguation of authors. This study emphasized inconsistencies in affiliation information, underscoring the need for institutional support and interoperability to ensure the completeness and accuracy of profiles (Fernández-Marcial et al, 2023). Similarly, at Emory University's School of Law, the challenges faced in promoting the adoption of ORCID among legal researchers were identified, given that their publishing and communication models are more traditional than in the sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, the Faculty of Arts and Humanities at the University of Porto showed a high ORCID adoption rate (90.4%), but the records were often incomplete, impacting the disambiguation of authors. This study emphasized inconsistencies in affiliation information, underscoring the need for institutional support and interoperability to ensure the completeness and accuracy of profiles (Fernández-Marcial et al, 2023). Similarly, at Emory University's School of Law, the challenges faced in promoting the adoption of ORCID among legal researchers were identified, given that their publishing and communication models are more traditional than in the sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the adoption of ORCID as a PID for unique author identification is becoming increasingly common (Haak et al, 2012), there are several challenges that researchers face when working with ORCID as a data source for scientometric studies. For example, there is a significant lack of adoption and completeness in ORCID records that varies across disciplines (Fernández-Marcial et al, 2023), the hard sciences tend to lead in adoption and completeness, in contrast to the social sciences, arts, and humanities (Boudry & Durand-Barthez, 2020;Bordons et al, 2024), and also across countries which leads to biases in coverage (Youtie et al, 2017). Previous studies have identified quality data issues such as empty records, problems with homonyms, sections with outdated data, multiple profiles for the same author (Heusse & Cabanac, 2022;Wang et al, 2024); the occurrence of duplicate and fake profiles Teixeira da Silva, 2021a;2021c), the creation of profiles by personnel not directly linked to research (Heusse & Cabanac, 2022), regular update of profiles (Costas et al, 2022), misidentification of authors and their associated institutions (Martínez-Méndez & Lopez-Carreño, 2019), the creation of "silent" or 'ghost' profiles (Teixeira da Silva, 2021a;Wang et al, 2024) and the limitations in data verification (Wang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Cette différence met en lumière une utilisation d'ORCID très spécifique par certains chercheurs, qui l'utilisent très certainement comme une porte d'entrée afin d'accéder à certains services sans pour autant que leur profil ne contienne la moindre information. ce manque de complétude des profils souligne bien l'implication moins grande à maintenir un compte ORCID qu'à le créer (Fernandez-Marcial et al, 2023). Ou encore : L'obligation de création d'un ORCID pour l'auteur soumettant ou correspondant, parfois pour tous les auteurs, devient de plus en plus courante lors de la soumission de manuscrits.…”
Section: Périodicité De Connexion Sur Le Compte Orcidunclassified
“…D'autres verbatims, de leur côté, signalent plus particulièrement des points ou des méconnaissances posant problème avec ces outils : types d'informations à mettre, fusion possible de plusieurs comptes doublons, alimentation automatique du compte, interopérabilité entre les services par exemple. Pour les institutions, un enjeu important touche à la qualité des données permettant d'identifier sans ambiguïté les chercheurs et les données touchant à l'institution (Boudry & Durand-Barthez, 2020;Fernandez-Marcial et al, 2023)…”
Section: Périodicité De Connexion Sur Le Compte Orcidunclassified
See 1 more Smart Citation